Developing Effective Customer Service Employees through Action Re-search : A Malaysian Local Authority Experience - Peter, Songan; Elizabeth, Loh; Abang Ekhsan, Abang Othman (UNIMAS Publisher, 2016)
Launching a hotline service is just one stage in the process of dealing with customers. Crucial to meeting its objectives is the development of human resources to imple-ment the hotline. This is to ensure that quality and standard are demonstrated in or-der to justify its existence. This paper presents the findings and reflection of an ac-tion research intervention to improve the Hotline Complaint Service of a local au-thority, the Kuching City South Council in Sarawak, Malaysia. The action research process in this study involved five mini cycles of planning, acting, observing and reflecting. Visits, participant observations, interviews and questionnaires were used in the data collection process. The data were analyzed using content analysis, and the findings validated through triangulation methods. The findings suggest that there was still room for improvement in the Council’s Complaint Service. An on-the-job experience for the hotline staff was implemented during which a guideline called the “13 Basic Principles in Effective Telephone Handling”; a “Handbook” on services provided by the Public Cleansing Division; and “Form A” were created and imple-mented. This study shows that action research is an important component of human resource development interventions that provides employees the opportunity to ac-quire the knowledge and skills through on-the-job experience to improve their per-formance and enhance the efficiency and productivity of their organization.